Spontaneous Pneumothorax: A Complication of Coronavirus Disease 2019 (COVID-19) Patients - Guo, Qiannan; Yang, Peiwen; Barnabo Nampoukime, Kan-paatib; Ma, Ke; Wang, Haihao (The Thoracic and Cardiovascular Surgeon, 2020)
Background At present, the coronavirus disease 2019 (COVID-19) is spreading all over the world. The occurrence of spontaneous pneumothorax in these patients might be higher than the fact, and we should pay high clinical attention to them.Method Data regarding clinical investigation, laboratory investigation, diagnosis, and treatment measures of 21 COVID-19 patients with spontaneous pneumothorax from January to March of 2020 were collected and analyzed in this study.Results Seven patients had a history of basic lung diseases. All patients used different methods of oxygen therapy before the occurrence of spontaneous pneumothorax according to the severity of the COVID-19, including 18 patients with ventilator-assisted breathing, 2 patients with bilevel positive airway pressure assisted breathing, and 1 patient with mask oxygen inhalation. All patients were confirmed cases of COVID-19 by chest CT (computed tomography) and virus nucleic acid detection and were found to have spontaneous pneumothorax through physical examination, bedside X-ray, and/or bedside ultrasound. 13 of 21 patients combined with pleural effusion at the same time. All the patients underwent closed thoracic drainage for spontaneous pneumothorax and the pleural effusion, if any. Nine patients died, and 12 patients recovered smoothly.Conclusion Spontaneous pneumothorax might be an overlooked complication of COVID-19 patients and may be associated with poor prognosis.
Keywords: COVID-19; spontaneous pneumothorax; closed thoracic drainage; poor prognosis